2021
DOI: 10.1111/ijcp.14143
|View full text |Cite
|
Sign up to set email alerts
|

Advisability of primary intraocular lens implantation for infants under 2: A systematic review and meta‐analysis

Abstract: Purposes The present meta‐analysis compared the postoperative visual performance of primary intraocular lens (IOL) implantation and primary aphakia in cataract infants. Methods PubMed, Embase, Science Direct and Cochrane Library were searched, and postoperative visual acuity (VA) and complications were extracted and pooled. Results Three randomised controlled trails (RCTs) and five retrospective studies were included. The postoperative VA of children younger than 4.5 years in primary IOL group was better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Some authors found that primary IOL implantation after pediatric cataract surgery is associated with a higher risk of postoperative RD. 18,33,34 However, Inoue et al reported that IOL implantation after cataract surgery decreased the incidence of postoperative RD. 35 The relationship between IOL https://doi.org/10.2147/OPTH.S464005…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors found that primary IOL implantation after pediatric cataract surgery is associated with a higher risk of postoperative RD. 18,33,34 However, Inoue et al reported that IOL implantation after cataract surgery decreased the incidence of postoperative RD. 35 The relationship between IOL https://doi.org/10.2147/OPTH.S464005…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that primary IOL implantation after pediatric cataract surgery is associated with a higher risk of postoperative RD. 18 , 33 , 34 However, Inoue et al reported that IOL implantation after cataract surgery decreased the incidence of postoperative RD. 35 The relationship between IOL implantation following pediatric cataract surgery and the risk of RD appears to be influenced by a variety of factors, including the surgical approach and individual patient characteristics, such as axial myopia.…”
Section: Discussionmentioning
confidence: 99%